Os traumas da violência patriarcal em Lya Luft - Santos, Maria Juliana de Jesus (2019)
This dissertation has the objective to intensify how the voices different evidence forms of sexual and psychological harassment cause emotional disturbances on the As parceiras (1980) romance feminine characters, from Lya Luff. The violence against the women confuses with the violence against the patriarchy, emphasized failed marriages of three different generations of this work: grandmother, Catarina, the mother Norma and the storyteller Anelise. For that propose we explored a feminine approach which revises the literary texts form interdisciplinary concepts about the violence against the woman over the patriarcal family. Methodologically, we explored concepts as the “masculine domination” from P. Bourdieu, “Masculinity excess” proposed by L. Machado, “disciplined body” from E. Xavier and “The rape relativization” from C. Gomes. This work’s structure is composed by three chapters which explain about the feminist study importance to a patriarcal concepts review and also propose an interpretation of the feminist character’s psychological marks as a patriarcal violence trauma. In the first chapter, we valorized the feminist study methodological approach to decentralize the genre identity concepts according to C. Duarte and J. Butler. In the second chapter, we brought the L. Hutcheon’s parody concept and S. Santiago’s postmodern narrator to analyze the intersection between the storyteller’s voice and the grandmother’s one as a postmodern aesthetic double mark: The metanarrativity and political engagement. In the last one, we analyzed the woman’s speech place, proposed by G. Spivak and D. Ribeiro to explore the technique used by the narrator, giving voice to the family’s silenced women meanwhile wants to find it in the actual days. We concluded that the revisionist debates proposed by the feminism are indispensable to amplify the interpretation of violence against the woman over the literary texts.